Unlocking Profitability: Exploring the Impact of Bank-Specific and Macroeconomic Determinants on Return on Equity in Commercial Banking Sector of Bangladesh - Rumaly, Nishat (International Journal of Economics and Financial Issues, 2023)
This study investigates the factors influencing Return on Equity (ROE) within the banking sector of Bangladesh by analyzing a comprehensive dataset spanning from the year 2011 to 2020. Utilizing a combination of econometric techniques, including the one-step difference GMM, Driscoll-Kraay estimator, and Panel-Corrected Standard Errors (PCSE) methods, this study analyzes the influence of various bank-specific and macroeconomic variables. The findings reveal a nuanced pattern of impact on ROE. Earnings Per Share (EPS), Capital Adequacy Ratio (CAR), and Bank Spread exhibit a significant positive influence on ROE, reflecting the importance of profitability, capital strength, and interest rate spreads. Conversely, asset size, operating cost-to-loans ratio, total equity-to-debt ratio, and inflation exert a significant negative impact on ROE, highlighting the challenges associated with growth, cost efficiency, leverage, and inflationary pressures. These findings provide a multifaceted perspective on the dynamics of ROE, offering valuable insights for banks and policymakers striving to optimize financial performance and stability in the ever-changing economic landscape.